2014
DOI: 10.1074/jbc.m114.572495
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Regulate Neutrophil Activation by Generating ATP for Autocrine Purinergic Signaling

Abstract: Background: Purinergic signaling regulates neutrophil activation. The source of ATP required for this process is unknown. Results: Mitochondria form the ATP that initiates purinergic signaling, and glycolysis provides the ATP that sustains functional responses of activated neutrophils. Conclusion: Mitochondrial ATP has a central role in triggering neutrophil activation. Significance: Mitochondria are regulators of the innate immune defense provided by neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 42 publications
4
128
0
Order By: Relevance
“…Recently, other evidence has emerged in support of a similar role for mitochondria in tumorigenesis [35][36][37]. We previously reported that mitochondria are central components of the purinergic signaling mechanisms that regulate immune cell functions [13,17,38,39]. Our current results show that highly active mitochondria in Jurkat cells upregulate the purinergic signaling processes that regulate cell metabolism and promote the proliferation of Jurkat cells.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, other evidence has emerged in support of a similar role for mitochondria in tumorigenesis [35][36][37]. We previously reported that mitochondria are central components of the purinergic signaling mechanisms that regulate immune cell functions [13,17,38,39]. Our current results show that highly active mitochondria in Jurkat cells upregulate the purinergic signaling processes that regulate cell metabolism and promote the proliferation of Jurkat cells.…”
Section: Discussionsupporting
confidence: 63%
“…Activation of the P2X1 receptor requires extracellular ATP. Unlike well-established mechanisms of platelets releasing ATP through degranulation of dense granule constituents, activated neutrophils release ATP primarily through membrane Cx43 hemichannels and gap junction protein pannexin 1 (Panx1) channels, as described in previous reports (14,15). The present study demonstrated that LPS promoted neutrophils releasing ATP through the Cx43 hemichannels because the Cx43 inhibitor but not the Panx1 inhibitor decreased ATP release ( Fig.…”
Section: Atp Is Released From Lps-stimulated Neutrophils Via Cx43 Hemsupporting
confidence: 51%
“…specifically, there are multiple ATP release pathways in neutrophils, including the secretion of granules that store ATP, as the amount of ATP released is dependent on the concentration of the chemoattractant (13). These studies suggest the existence of granule-mediated ATP exocytosis.…”
mentioning
confidence: 83%